PENGARUH BEBAN KERJA, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT. ROMI VIOLETA - Ratna Melinda Putri; Endang Iryanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Employee performance is the most important factor or key to determine the success of a company, in achieving planned goals. Issues related to performance are the main concern in this study. The purpose of the study was to identify the impact of workload, work discipline, and organizational commitment on employee performance at PT. Romi Violeta. The method used is a quantitative method with a sample involving 51 permanent employees in the general administration, production and marketing departments. Data were obtained through distributing questionnaires using a Likert scale from 1 to 5 and processed using the SmartPLS program analysis. The results of this study indicate that workload has a negative effect on employee performance. Meanwhile, work discipline and organizational commitment have a positive effect on employee performance. Increasing workload can cause a decrease in employee performance. While increasing work discipline and organizational commitment, employee performance will increase. Keywords: workload, work discipline, organizational commitment, employee performance